A Case of Musical Hallucinations Related to Mirtazapine. Issue 6 (November 2018) - Lee, Grace H.; Stewart, Jonathan T.
Abstract : Abstract: Musical hallucinations (MHs) are relatively uncommon phenomena sometimes encountered in older patients, especially older women. They usually involve popular, overlearned music, either entire songs or repetitive snippets. While MHs are most commonly associated with hearing loss, they may occur in a variety of psychiatric, neurologic, and iatrogenic conditions. We report a 91-year-old man whose MHs were causally related to the antidepressant mirtazapine. Although mirtazapine is generally well tolerated, it may rarely cause MHs or other psychotic symptoms.